Dipolar SAMs reduce charge carrier injection barriers in n-channel organic field effect transistors - Jesper, Malte; Hillebrandt, Sabina; Rohnacher, Valentina; Pucci, Annemarie; Lemmer, Uli; Kowalsky, Wolfgang; Glaser, Tobias; Lovrinčić, Robert; Hamburger, Manuel; Bunz, Uwe H. F. (Langmuir, 2015)
In this work we examine small conjugated molecules bearing a thiol headgroup as self assembled monolayers (SAM). Functional groups in the SAM-active molecule shift the work function of gold to n-channel semiconductor regimes and improve the wettability of the surface. We examine the effect of the presence of methylene linkers on the orientation of the molecule within the SAM. 3,4,5-Trimethoxythiophenol (TMP-SH) and 3,4,5-trimethoxybenzylthiol (TMP-CH2-SH) were first subjected to computational analysis, predicting work function shifts of −430 and −310 meV. Contact angle measurements show an increase in the wetting envelope compared to that of pristine gold. Infrared (IR) measurements show tilt angles of 22 and 63°, with the methylene-linked molecule (TMP-CH2-SH) attaining a flatter orientation. The actual work function shift as measured with photoemission spectroscopy (XPS/UPS) is even larger, −600 and −430 meV, respectively. The contact resistance between gold electrodes and poly[N,N′-bis(2-octyldodecyl)-naphthalene-1,4:5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene) (Polyera Aktive Ink, N2200) in n-type OFETs is demonstrated to decrease by 3 orders of magnitude due to the use of TMP-SH and TMP-CH2-SH. The effective mobility was enhanced by two orders of magnitude, significantly decreasing the contact resistance to match the mobilities reported for N2200 with optimized electrodes.